REPRESENTASI KONFLIK BATIN TOKOH UTAMA NOVEL CRITICAL ELEVEN: KAJIAN PSIKOLOGI SASTRA: REPRESENTASI KONFLIK BATIN TOKOH UTAMA NOVEL CRITICAL ELEVEN: KAJIAN PSIKOLOGI SASTRA - Anike Agustina Assem, Anike Agustina Assem (FRASA: Jurnal Keilmuan, Bahasa, Sastra, dan Pengajarannya, 2026)
Literary works, especially novels, serve as important mediums for representing human psychological dynamics. Studies on literary psychology of contemporary Indonesian novels, particularly those addressing trauma and inner conflict after loss, remain limited. This study aims to analyze aspects of literary psychology, forms of inner conflict, and their influence on main character development in Ika Natassa's novel Critical Eleven. Method is descriptive qualitative research with literary psychology approach using Freud's psychoanalysis theory and modern psychology theories (2014-2024). Data were collected through close reading techniques from the novel text and analyzed using Miles, Huberman, & Saldaña model. Results show that inner conflicts of Anya and Ale emerge through six aspects of literary psychology: basic emotions, traumatic memory, intrapsychic conflict, psychological trauma, emotion regulation, and relational psychological needs. Inner conflicts experienced include contradictions between hope-reality, desire to recover-guilt, need for closeness-avoidance, and logic-emotion. Inner conflict functions as catalyst for character transformation that deepens emotional dimensions, improves interpersonal relationship quality, and develops characters' existential understanding. These findings enrich contemporary literary psychology studies in understanding trauma dynamics, emotion regulation, and couple resilience facing loss.